2021
DOI: 10.5603/ep.a2021.0077
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin measurements in washouts of fine-needle aspiration biopsy in the monitoring of patients with differentiated thyroid carcinoma

Abstract: Introduction: Approximately 35% patients with papillary thyroid carcinoma (PTC) and 13% with follicular thyroid carcinoma (FTC) present with metastases of cervical lymph nodes (LNs) at the time of diagnosis. In addition, 15-20% of patients treated with total thyroidectomy develop, after an interval of five years, metastases to the neck LNs on ultrasound examination. Fine-needle aspiration biopsy (FNAB) represents the gold standard technique for the detection of cervical LNs metastases. The aim of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…23 As documented by Bakuła-Zalewska et al, who studied the role of Tg-FNAC in diagnosing lymph nodal metastases in patients with differentiated thyroid carcinoma (DTC), including both PTC and follicular thyroid carcinoma, Tg-FNAC combined with FNAC of suspicious lymph nodes in patients with DTC increased the diagnostic accuracy of FNAC (99% sensitivity and 99% specificity). 24 Another option to clarify the role of FNAC was suggested by Zhang et al 25 The authors compared FNAC and core needle biopsy The false-positive cases had a negative Tg-FNAC, but at the histological evaluation, we found another lymph node with a micrometastasis. The false-positive interpretation was due to the presence of a few cells resembling an epithelial morphology.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…23 As documented by Bakuła-Zalewska et al, who studied the role of Tg-FNAC in diagnosing lymph nodal metastases in patients with differentiated thyroid carcinoma (DTC), including both PTC and follicular thyroid carcinoma, Tg-FNAC combined with FNAC of suspicious lymph nodes in patients with DTC increased the diagnostic accuracy of FNAC (99% sensitivity and 99% specificity). 24 Another option to clarify the role of FNAC was suggested by Zhang et al 25 The authors compared FNAC and core needle biopsy The false-positive cases had a negative Tg-FNAC, but at the histological evaluation, we found another lymph node with a micrometastasis. The false-positive interpretation was due to the presence of a few cells resembling an epithelial morphology.…”
Section: Discussionmentioning
confidence: 85%
“…The authors suggested that with a sensitivity of 86.6%, Tg‐FNAC is likely to be used as an adjunct to FNAC alone 23 . As documented by Bakuła‐Zalewska et al., who studied the role of Tg‐FNAC in diagnosing lymph nodal metastases in patients with differentiated thyroid carcinoma (DTC), including both PTC and follicular thyroid carcinoma, Tg‐FNAC combined with FNAC of suspicious lymph nodes in patients with DTC increased the diagnostic accuracy of FNAC (99% sensitivity and 99% specificity) 24 …”
Section: Discussionmentioning
confidence: 94%
“…Многие авторы принимали минимальный порог ТГ ≤1 нг / мл, исходя из соображений, что в норме ТГ в ЛУ быть не должно [6,12]. Некоторые исследователи использовали ROC-анализ для выбора порогового значения ТГ при оптимальных чувствительности и специфичности [13]. Предлагалось также использовать различные пороговые значения для пациентов после тиреоидэктомии и с сохраненной ЩЖ [14].…”
Section: Discussionunclassified
“…В результате, чувствительность и специфичность для ТАБ составили 97 и 99 %; для ТАБ-ТГ -92 и 93 %; при их комбинации (ТАБ + ТАБ-ТГ) -99 % соответственно. Таким образом, сочетание ТАБ + ТАБ-ТГ увеличило чувствительность по сравнению с изолированной ТАБ или ТАБ-ТГ [9].…”
Section: êëèíè×åñêèå èññëåäîâàíèßunclassified